Time trends in post-polypectomy surveillance guideline adherence: analysis of over 90 000 colonoscopies with polypectomy - Zessner-Spitzenberg, Jasmin; Penz, Daniela; Waldmann, Elisabeth; Bognar, Florian; Unger, Sarah; Selinger, Theresa; Demschik, Alexandra; Trauner, Michael; Ferlitsch, Monika (Endoscopy, 2025)
Previous studies found poor adherence to guidelines on post-polypectomy care. We aimed to investigate adherence to the European Society of Gastrointestinal Endoscopy (ESGE) recommendations before and after publication of the updated guideline in 2020, stratified by polyp type.Participants undergoing screening documented in the Austrian Quality Certificate for Screening Colonoscopy program were included in the study. Piecewise linear regression with one breakpoint was applied to investigate trends in guideline adherence. A mixed-effects logistic regression model was fitted to investigate the associations of screening participant and endoscopist characteristics with guideline adherence.Between August 2020 and November 2024, adherence to the post-polypectomy guideline increased by 49% (95%CI 19%–86%). The strongest improvement in surveillance interval adherence was observed for adenomas (38.4% in 2020 vs. 51.2% in 2024); adherence for serrated polyps only marginally improved (52.4% in 2020 vs. 54.3% in 2024). There was a positive association between endoscopists’ adenoma detection rate (ADR) and the probability of adherence to the ESGE guideline for surveillance of high risk polyps; however, the effect size was only modest (odds ratio 1.01, 95%CI 1.00–1.03).An improvement of up to 49% in ESGE guideline adherence was observed over 4 years after publication of the update, which was mostly driven by improved adherence to the surveillance intervals for adenomas. Endoscopists with higher ADRs were more likely to assign correct follow-up intervals.